The influence of lung metastases on the clinical course of gestational trophoblastic neoplasia: a historical cohort study. (12th October 2015) - Vree, M; van Trommel, N; Kenter, G; Sweep, F; ten Kate‐Booij, M; Massuger, L; Lok, C
Abstract : Objective: To evaluate whether gestational trophoblastic neoplasia (GTN) patients with lung metastases have more adverse outcomes such as resistance to chemotherapy, recurrence or death of disease compared with patients without lung metastases. Design: Historical observational cohort study. Setting: The Netherlands. Population: We identified 434 GTN patients (72 patients with lung metastases, 362 patients without metastases) between 1990 and 2012 registered in the Dutch national databases. Methods: Baseline characteristics, recurrence rates, Methotrexate (MTX) remission rates and deaths from disease were compared between patients with lung metastases (group I) and without lung metastases (group II) using the Fisher exact test or Mann–Whitney U ‐test where applicable. Main outcome measures: Methotrexate resistance, recurrences and survival. Results: Methotrexate resistance did not differ between group I and group II (62.9 versus 72.7% P = 0.19). However, the observed recurrence rate was significantly increased in patients with lung metastases compared with patients without metastases (16.7 versus 2.2% P < 0.0001), also after correction for antecedent pregnancy and interval (from the end of the antecedent pregnancy until the start of treatment). Disease‐specific survival was 91.7% in the group with lung metastases and 100% in the patients without metastases ( P < 0.0001). Conclusions: Although lung metastases are considered to be associated with a low risk of adverse outcomes, their presence appears to increase the risk for recurrence and death of disease. Further research is needed to evaluate whether the presence of lung metastases is an independent risk factor that needs adjustment in the FIGO scoring system and clinical classification system. Tweetable abstract: In gestational trophoblastic neoplasia (GTN) recurrence is more often observed in the case of lung metastases. Tweetable abstract: In gestational trophoblastic neoplasia (GTN) recurrence is more often observed in the case of lung metastases.